Zircon U–Pb age, geochemistry and Sr‐Nd‐Hf isotopes of the Baolige granite complex in the Great Hingan Range, NE China. (15th September 2017) - Zhu, Xue‐Feng; Chen, Yan‐Jing; Wang, Pin; Wang, Shou‐Xu; Zhang, Cheng
Abstract : The Solonker zone is widely accepted as the suture between the North China Craton and the Siberia–Mongolia continental plate. The Baolige granite complex is located to the north side of the Solonker Suture and is mainly composed of monzogranite and granite. Zircon U–Pb ages, geochemistry, and Sr‐Nd‐Hf isotopic data of the Baolige granites were presented to constrain their petrogenesis and tectonic settings. Two monzogranite samples from Baolige yielded weighted mean zircon 206 Pb/ 238 U ages of 310.7 ± 2.1 Ma (mean square of weighted deviates (MSWD) = 1.3) and 307.4 ± 1.6 Ma (MSWD = 0.77), whereas the granite intruded into the monzogranite yielded an age of 296.2 ± 2.0 Ma (MSWD = 1.2). Both the Baolige monzogranite and granite contain high contents of SiO2, K2 O, and Al2 O3, low contents of TiO2, MgO, and CaO, and are peraluminous high‐K calc‐alkaline. These rocks are characterized by enrichments of K, Rb, U, Pb, Th, and light rare earth elements and depletions of Nb, Ta, Ti, and heavy rare earth elements and contain slightly negative or no Eu anomalies, similar to typical arc‐related granitoids. The Ti‐in‐zircon thermometry yielded 650–759 °C for the monzogranite and 645–796 °C for the granite. The monzogranite shows positive zircon εHf (t) values (4.7–13.2) and whole‐rock εNd (t) values (3.6–5.2), with TDM2(Hf) ages of 1, 324–557 Ma and TDM2(Nd) ages of 1, 015–821 Ma, and ISr of 0.70363–0.70386. The granite shows εHf (t) values of 15.6–20.9 and εNd (t) values of 4.0–5.1, with TDM2(Nd) ages of 957–832 Ma, and ISr of 0.70364–0.70406. Geochemical evidence indicates that the Baolige granite complex is highly fractionated I‐type and was likely formed by partial melting of the Neoproterozoic juvenile crust in a continental arc setting. We concluded that the Paleo‐Asian Ocean may have undergone north‐dipping subduction beneath the Siberia–Mongolia continental plate during the Late Carboniferous, and the subduction may have continued to the Early Permian (ca. 296 Ma).